The structural, dynamic, and thermodynamic basis of darunavir resistance of a heavily mutated HIV-1 protease using molecular dynamics simulation - Shabanpour, Yaser; Sajjadi, Sharareh; Behmard, Esmaeil; Abdolmaleki, Parviz; Keihan, Amir Homayoun (Frontiers in Molecular Biosciences, 2022)
The human immunodeficiency virus type 1 protease (HIV-1 PR) is an important enzyme in life cycle of the HIV virus. It cleaves inactive pre-proteins of the virus and changes them into active proteins. Darunavir (DRV) suppresses the wild type HIV-1 PR (WT-Pr) activity, but can’t inhibit some mutant resistant forms (MUT-Pr). Increasing knowledge about the resistance mechanism can be helpful for designing of more effective inhibitors. In this study, the mechanism of resistant of a highly MUT-Pr strain against DRV was investigated. For this purpose, complexes of DRV with WT-Pr (WT-Pr-D) and MUT-Pr (MUT-Pr-D) were studied by all-atom molecular dynamics simulation in order to extract the dynamic and energetic properties. Our data revealed that mutations increased the flap-tips flexibility due to the reduction of the flap-flap hydrophobic interactions. So, the protease’s conformation changed from a closed state to a semi-open state that can facilitate the disjunction of DRV from the active-site. On other side, energy analysis limiting to final basins of the energy landscape indicated that the entropy of binding of DRV to MUT-Pr was more favorable than that of WT-Pr. However, the enthalpy penalty overcome it and made binding more unfavorable relative to the WT-Pr. The unfavorable interaction of DRV with R8, I50, I84, D25’ and A28’ residues in MUT-Pr-D relative to WT-Pr-D are reason of this enthalpy penalty. Thus mutations drive resistance to DRV. The hydrogen bonds analysis showed that compare with WT-Pr, the hydrogen bonds between DRV and the active-site residues of MUT-Pr were disrupted.